2020
DOI: 10.2196/20656
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact of Health Risk Communication and Social Media on College Students During the COVID-19 Pandemic: Cross-Sectional Study

Abstract: Background The outbreak of COVID-19 began in 2019 and is expected to impact the psychological health of college students. Few studies have investigated the associations among health risk communication, social media, and psychological symptoms during a major pandemic. Objective The aim of this research was to assess the prevalence of psychological symptoms among college students and explore their associations with health risk communication and social media. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 54 publications
0
36
1
1
Order By: Relevance
“…Knowing and correctly using RPE is important not only in terms of reducing the risk of infection, but also reducing the level of health concern and anxiety. We did not question participants regarding their psychophysiological state in this study, but researchers from China found that knowledge regarding means of protection, along with prognosis of the epidemiological situation and preventive measures, are protective factors against health concerns [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Knowing and correctly using RPE is important not only in terms of reducing the risk of infection, but also reducing the level of health concern and anxiety. We did not question participants regarding their psychophysiological state in this study, but researchers from China found that knowledge regarding means of protection, along with prognosis of the epidemiological situation and preventive measures, are protective factors against health concerns [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, it was difficult to conduct a field survey due to the impacts of COVID‐19. However, online survey became a feasible and popular method to collect data (Li et al, 2020; Yun et al, 2020) during COVID‐19 epidemic. On the other hand, the research object of this study was residents, and samples are large geographically dispersed.…”
Section: Methodsmentioning
confidence: 99%
“… 36 Similar findings concerning the impact of risk communication messages on college students’ behavior from China were reported. 37 This study also finds that the general Saudi population has an adequate understanding of knowledge areas about COVID-19. The responders correctly identified the main symptoms of COVID-19 38 , 39 and high-risk populations.…”
Section: Discussionmentioning
confidence: 54%